2014
DOI: 10.3109/09273948.2014.928734
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Choroidal Thickness in Ankylosing Spondylitis Using Optical Coherence Tomography

Abstract: This is the first study to evaluate effects of AS on CT. CT was high in patients with AS compared to healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…OCT has been used to evaluate choroid thickness in patients with a number of systemic autoimmune and inflammatory disorders (9)(10)(11)(12)(13) . Patients with active Vogt-Koyanagi-Harada disease have been shown to have markedly increased choroidal thickness, possibly related to inflammatory infiltration and increased exudation (9) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…OCT has been used to evaluate choroid thickness in patients with a number of systemic autoimmune and inflammatory disorders (9)(10)(11)(12)(13) . Patients with active Vogt-Koyanagi-Harada disease have been shown to have markedly increased choroidal thickness, possibly related to inflammatory infiltration and increased exudation (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Gungor et al reported patients with posterior ocular sarcoidosis in the absence of active ocular inflammation had decreased choroidal thickness compared to normal subjects during the quiescent phase of the disease (12) , however, the authors were unable to provide a satisfactory explanation for this finding. Kola et al reported increased choroidal thickness in patients with ankylosing spondylitis compared to healthy controls (13) . The authors proposed that chronic systemic inflammation may play an important role in the thickening of the choroid layer in patients with ankylosing spondylitis (13) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 In our study in question we examined choroidal thickness values in cases of ankylosing spondylitis. 2 That study showed that the choroid can be affected in ankylosing spondylitis.…”
mentioning
confidence: 99%